1990
DOI: 10.1038/ki.1990.280
|View full text |Cite
|
Sign up to set email alerts
|

Effects of probucol on renal function in rats with bilateral ureteral obstruction

Abstract: To ascertain the potential role of reactive oxygen metabolites in the pathophysiology of obstructive uropathy, we examined the effect of probucol, an antioxidant agent, on renal function in normal rats and rats with unilateral release of bilateral ureteral obstruction (BUO) of 24 hours duration. Rats were fed either a standard diet or a standard diet containing one percent probucol for two weeks prior to study. Probucol lowered serum cholesterol in both normal and BUO rats. Probucol did not significantly affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
1

Year Published

1993
1993
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 24 publications
1
37
0
1
Order By: Relevance
“…ROS cause tissue injury directly, such as by cleavage of peptide bonds (10), or indirectly by initiating myeloperoxidase-H202-halide reactions ( 11), or by lipid peroxidation (LPO) which results, among other consequences, in the generation of highly reactive aldehydes which can then complex with lysine residues of proteins (10)(11)(12)(13). Since there is evidence for the involvement of ROS in experimental renal diseases (7,8,11,14,15), we have examined the contribution of LPO to the development of proteinuria in PHN.…”
Section: Introductionmentioning
confidence: 99%
“…ROS cause tissue injury directly, such as by cleavage of peptide bonds (10), or indirectly by initiating myeloperoxidase-H202-halide reactions ( 11), or by lipid peroxidation (LPO) which results, among other consequences, in the generation of highly reactive aldehydes which can then complex with lysine residues of proteins (10)(11)(12)(13). Since there is evidence for the involvement of ROS in experimental renal diseases (7,8,11,14,15), we have examined the contribution of LPO to the development of proteinuria in PHN.…”
Section: Introductionmentioning
confidence: 99%
“…Studies from our laboratory have suggested that the glomerular physiologic and tubular effects of inhibition of nitric oxide synthase with L-NMMA is greatly influenced by previous renal denervation (43). Additional studies have suggested that this may be due to an ␣ 2 -adrenergic effect (44). Phentolamine blocks both ␣ 1 -and ␣ 2 -adrenergic activity.…”
Section: Discussionmentioning
confidence: 97%
“…Phentolamine blocks both ␣ 1 -and ␣ 2 -adrenergic activity. Probucol has also been suggested to alter the development of glomerulosclerosis in a subtotal nephrectomy model (44). Mechanisms that form the basis for this prevention of glomerulosclerosis have not been fully delineated.…”
Section: Discussionmentioning
confidence: 99%
“…22 Modi showed that the levels of MDA were significantly higher in rats with ureteral obstruction compared with the sham-treated group. 23 In response to ROS, anti-oxidant enzymes including catalase, SOD are thought to protect cellular function. Deficiency of these anti-oxidant enzymes could enhance ROS production and renal tubulointerstitial fibrosis.…”
Section: Discussionmentioning
confidence: 99%